The effect of corporate entrepreneurship on the perceived financial performance of established Malaysian state government-linked corporations / Sofian Shamsuddin - Shamsuddin, Sofian (Institute of Graduate Studies, UiTM, 2012)
Over recent years, much government efforts have been concentrated on enhance ng innovation and entrepreneurship. This stems from the view that organizations profit from the influences of corporate entrepreneurship and innovation. Thus the choice of whether to grow corporate entrepreneurship and how it may result in variation in performance is an eminent issue. Paying special attention to this trend provides the basis for this study. Using data from 92 out of 102 intrapreneur companies largely founded within the past fifteen years and across diverse industries such as construction, plantation, property, technology and trading/services, this study analyzes the effect of corporate entrepreneurship dimensions on the perceived financial performance of established Malaysian state government-linked corporations. In particular, the research attempts to: (1) determine the effect of corporate entrepreneurship (CE) dimensions on company performance, and (2) explore the moderating effects of resource availability, supportive organizational structure and rewards have on the relationship between CE dimensions and company performance.